Efficient Capture of Organic Dyes and Crystallographic Snapshots by a Highly Crystalline Amino‐Acid‐Derived Metal–Organic Framework. Issue 67 (25th September 2018) - Mon, Marta; Bruno, Rosaria; Tiburcio, Estefanía; Casteran, Pierre‐Edouard; Ferrando‐Soria, Jesús; Armentano, Donatella; Pardo, Emilio
Abstract: The presence of residual organic dyes in water resources or wastewater treatment systems, derived mainly from effluents of different industries, is a major environmental problem with no easy solution. Herein, an ecofriendly, water‐stable metal–organic framework was prepared from a derivative of the natural amino acidl ‐serine. Its functional channels are densely decorated with highly flexiblel ‐serine residues bearing hydroxyl groups. The presence of such a flexible and functional environment within the confined environment of the MOF leads to efficient removal of different organic dyes from water: Pyronin Y, Auramine O, Methylene Blue and Brilliant Green, as unveiled by unprecedented snapshots offered by single‐crystal X‐ray diffraction. This MOF enables highly efficient water remediation by capturing more than 90 % of dye content, even at very low concentrations such as 10 ppm, which is similar to those usually found in industrial wastewaters. Remarkably, the removal efficiency is improved in simulated contaminated mineral water with multiple dyes. Abstract : Multidye capture : A highly crystalline metal–organic framework, derived from the amino acidl ‐serine, captures efficiently different organic dyes at very low concentration, even in the presence of multiple dyes (see figure). In addition, single‐crystal X‐ray diffraction offered unprecedented snapshots of the dye‐capture process.